Evaluación de la concentración de material particulado de pm 2.5 y pm 10 en la Parroquia La Matriz en el Cantón Latacunga, Provincia de Cotopaxi en el período 2018 – 2019 - Rodríguez Castro, Jason Cristhian (2019)
Deterioration, once the respective monitoring was carried out, the database was obtained and compared with Ecuadorian Regulations, Book VI Annex 4, which tells about the permissible limits of emissions of particulate matter for PM10 with a value of 100 ug / m3 and for PM2.5 is 50 ug / m3. In the Sector of El Salto square was found that 2:00 pm is the peak hour where PM10 particulate material is in greater quantity with 79 ug / m3 and the following peaks are at 7:00 pm with 22 ug / m3 and 8:00 pm with 24 ug / m3 obtaining an average of 13.17 ug / m3; for the PM2.5 particulate material, the highest peak was found at 9:00 p.m. with 15 ug / m3, the following peaks were at 6:00 p.m. with 12 ug / m3 and 7:00 p.m. with 14 ug / m3 with an average of 6.47ug / m3. In the town of San Agustín Square, the obtained values for PM10 particulate material, the highest peak was at 7:00 am with 24 ug / m3, the following peaks were at 24h00 pm with 23 ug / m3 and 10h00 am with 22 ug / m3 with an average of 14,13 ug / m3. For PM2.5 particulate material, the schedule with the highest pollution was at 01:00 am with 27 ug / m3, followed by 20h00 pm with 24 ug / m3, and 07h00 am with 22 ug / m3 an average of 14.60 ug / was obtained. m3. Comparing with the Legal Regulations is observed that in both locations there is great pollution in San Agustín square with averages of PM10 with 14.13 ug / m3 and PM2.5 with 14.60 ug / m3. It is concluded that the values obtained in each of the sampled locations are lower than PM10 (100 ug / m3) and PM2.5 (50 ug / m3) complying w